The Influence of Environmental Performance, Social Performance, and Governance Performance on the Financial Performance of Banking Companies Listed on the Indonesia Stock Exchange - Dewi Anggraini; Ridwan Nurazi; Fitri Santi; Berto Usman (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of environmental performance , social performance , and governance performance on the financial performance of banking companies listed on the Indonesia Stock Exchange for the period 2013–2022. This study uses a quantitative approach with secondary data obtained from company annual reports, financial reports, and the Thomson Reuters Refinitiv Asset4 database. The research sample was determined using a purposive sampling technique , while data analysis was carried out using a panel data regression method using the EViews 10 application. The results showed that environmental performance did not have a significant effect on financial performance as proxied by financial performance with the Return on Assets (ROA) approach with a probability value of 0.2978. Social performance also did not have a significant effect on financial performance with a probability value of 0.8998. Similarly, governance performance did not have a significant effect on financial performance with a probability value of 0.4320. These findings indicate that the implementation of environmental, social, and governance aspects in banking companies has not been able to directly increase profitability during the study period. The benefits of implementing these three aspects tend to be long-term, through improved corporate reputation, stakeholder trust, and enhanced business sustainability. Therefore, they are not yet fully reflected in improved financial performance. This research implies that banking companies need to continue strengthening the implementation of sustainability practices as a long-term strategy, while investors need to consider ESG aspects in addition to profitability indicators when evaluating company performance.